Rough and Tumbled — the Prehistoric Geoheritage Significance of Ogallala Formation Quartzarenite Clasts in Northwestern Texas - Stance Hurst; Doug Cunningham; Eileen Johnson (Geoheritage, 2026)

Shelters of Necessity: Exploring the Geoheritage of Dugout Architecture in Early Northwest Texas Settlement - Glenn G. Fernández-Céspedes; Stance Hurst; Doug Cunningham; Emily Ladd; Eileen Johnson (Geoheritage, 2026)
This study explores the geoheritage significance of dugouts constructed by early Anglo-American settlers across the Southern High Plains and Rolling Plains of Texas. Geoheritage, which in this study emphasizes the relationship between geodiversity and cultural adaptation, provides a framework to examine how settlers used locally available geological resources for shelter in response to environmental challenges. Fieldwork and archival research has documented 11 dugouts from buffalo hunters, cattle ranchers, sheepherders, and homesteaders. Analysis includes Geographic Information Systems (GIS) and photogrammetric modeling to evaluate the impact of geodiversity on dugout placement, construction materials, and design. Results reveal that most dugouts were constructed near critical resources such as water sources and rock outcrops, with sandstone from the Dockum Group being the most commonly used building material. Terrain sheltered from wind is prioritized, with 64% of dugouts located on slopes or near valleys, highlighting strategic responses to the Southern Plains climate. The variability in dugout dimensions and materials among cultural groups underscores the diverse ways settlers interacted with available resources, reflecting both immediate needs and cultural practices. This research advances geoheritage by demonstrating that even temporary, adaptive structures like dugouts contribute to the understanding of human interaction with geodiversity. By situating these shelters within a geoheritage framework, the study provides new insights into how early settlers adapted to and modified their landscapes, adding depth to the region’s cultural and geological legacy. The findings support a more inclusive view of geoheritage, encompassing permanent and transient human imprints on the landscape.